2023
DOI: 10.1128/spectrum.03029-23
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocapsid protein accumulates in renal tubular epithelium of a post-COVID-19 patient

Anita E. Grootemaat,
Niek Wiersma,
Sanne van der Niet
et al.

Abstract: In this study, we investigated whether severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral proteins and virus particles can be detected (i) in post-mortem kidney of fatal coronavirus disease 2019 (COVID-19) patients and (ii) in renal biopsy of patients suffering from kidney failure months after combating a SARS-CoV-2 infection. Using fluorescence microscopy, antibodies against viral proteins [nucleocapsid, membrane (M), non-structural proteins (nsp) 3, 4, and 13] and double-stranded RNA (dsRNA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Another aspect of canonical inflammation in LC, which was not included in the aims and objectives of our study, is considering LC as a risk factor for the onset of various inflammatory diseases or the progression of existing inflammatory diseases [ 323 , 324 , 325 , 326 , 327 ]. This primarily concerns immune-dependent diseases, whose association has been established, namely various allergic, autoimmune, and infectious diseases, but also should be taken into account in other pathological conditions as well [ 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 ,…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another aspect of canonical inflammation in LC, which was not included in the aims and objectives of our study, is considering LC as a risk factor for the onset of various inflammatory diseases or the progression of existing inflammatory diseases [ 323 , 324 , 325 , 326 , 327 ]. This primarily concerns immune-dependent diseases, whose association has been established, namely various allergic, autoimmune, and infectious diseases, but also should be taken into account in other pathological conditions as well [ 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 ,…”
Section: Methodsmentioning
confidence: 99%
“…It has been observed that the N protein of SARS-CoV-2 persists in the renal tubule epithelium of recovered COVID-19 patients. The presence of the N protein, even without signs of viral replication, may be significant for the recurrence of kidney disease and have lasting effects on the immune system [ 279 ].…”
Section: Local Phenomena Of Low-grade Inflammation In Lc and Other Vi...mentioning
confidence: 99%
“…In addition, more studies have demonstrated the presence of SARS-CoV-2 N protein accumulations in the kidney tubular epithelium of patients with COVID-19 [91,[109][110][111]. Another immunoelectron microscopy study revealed the accumulations of SARS-CoV-2 N protein in one patient previously diagnosed with COVID-19 three months prior to the manifestation of kidney failure [112]. Thus, the urinary SARS-CoV-2 N protein may serve as an indicator of the likelihood of AKI development, which may provide clinicians with insights into the severity of COVID-19 [113].…”
Section: Stage Descriptionmentioning
confidence: 99%